Sturgeon osteocalcin shares structural features with matrix gla protein evolutionary relationship and functional implications - S B Viegas, Carla (2013)
Osteocalcin (OC) and matrix Gla protein (MGP) are considered evolutionarily related because they share key structural features, although they have been described to exert different functions. In this work, we report the identification and characterization of both OC and MGP from the Adriatic sturgeon, a ray-finned fish characterized by a slow evolution and the retention of many ancestral features. Sturgeon MGP shows a primary structure, post-translation modifications, and patterns of mRNA/protein distribution and accumulation typical of known MGPs, and it contains seven possible Gla residues that would make the sturgeon protein the most gamma-carboxylated among known MGPs. In contrast, sturgeon OC was found to present a hybrid structure. Indeed, although exhibiting protein domains typical of known OCs, it also contains structural features usually found in MGPs (e. g. a putative phosphorylated propeptide). Moreover, patterns of OC gene expression and protein accumulation overlap with those reported for MGP; OC was detected in bone cells and mineralized structures but also in soft and cartilaginous tissues. We propose that, in a context of a reduced rate of evolution, sturgeon OC has retained structural features of the ancestral protein that emerged millions of years ago from the duplication of an ancient MGP gene and may exhibit intermediate functional features.